Cellular level classification of breast cancer through proteomic markers using nanochannel array sensors. (2014) - Panneer Selvam, Anjan; Wong, Justin; Flanagan, Kelly; Prasad, Shalini
Aims: A nanochannel-based sensor for cellular level classification of breast cancer metastasis has been designed. Our approach to the classification of cell's likelihood to metastasize is based on screening for levels of expression of specific proteomic biomarkers associated with breast cancer stem cells.Materials & methods: Proteomic activity for four breast cancer cell lines for three specific markers (PDGFR, ALDH1A1 and ALDH1A3) was quantified. The nanochannel sensor is an electrochemical immunoassay and comprises of alumina nanochannel arrays integrated on to a gold microelectronic platform. The sensor operates on the principle of electrochemical impedance spectroscopy.Results & conclusion: Test cell lysate samples from SUM159 invasive, SUM159 noninvasive, HC1143 and DCIS cell lines were classified as those having a high likelihood of metastases based on the levels of proteomic activity evaluated against the three key markers. The lowest proteomic activity measured was 0.1 ng/ml with PDGFR, 100 ng/ml with ALDH1A1 and 100 ng/ml with ALDH1A3, correlating to the detection of unit stem cell count. Original submitted 9 November 2012; Revised submitted 29 July 2013